Critical analysis on the syariah law that prohibits the consumption of alcohol among Muslims. The position of law in Malaysia with special reference to Brunei law / Nurhamizah Bustami … [et al.] - Bustami, Nurhamizah; Azmi, Aifa; Amrul Halim Gan, Farrah Emmylya; Abul Kamar, Nursyafiqah (Faculty of Law, 2014)
Malaysia, with twenty eight billion populations comprises sixteen per cent majority Malays, who are Muslims, has been ranked the tenth biggest consumer of alcohol in 2011 by the World Health Organization (WHO) despite the Syariah law that we have to combat such offence among the Muslims. Cases where Muslim youngsters are being caught consuming alcohol in public increase day by day, resulting to declination of health and morality. Being a country with majority of its population embraced the religion of Islam and with the existence of various legislations among the states to curb this offence, this problem should not have arisen. Hence, this research sought to study the efficiency of the law governing the said offence in Pahang, Kelantan, Selangor and Federal Territories as well as the possibility of enforcing a more severe punishment under Hudud law, which forms an integral part of Islamic criminal law as a solution to this problem. The research found that there is a possibility of such enforcement in Malaysia without having any constitutional issue arising. Nevertheless, in order for this solution to be possible the Syariah Courts (Criminal Jurisdiction) Act 1965, which does not have sentencing power of more than 3 years or with whipping exceeding six strokes or with fine for more than five thousands or with any combination of both, must be amended so as to increase the sentencing power of the states and subsequently, allow the states to enforce punishment of eighty strokes of whipping as has been prescribed under Hudud law. In conclusion, we recommend that such amendment should be made so that the law would not only be punitive in nature but also work as deterrence for the repeated offenders as well as future offenders.